High-rate Deformation and Spall Fracture of Some Metals. (2017) - Bragov, A.M.; Balandin, V.V.; Konstantinov, A.Yu.; Lomunov, A.K.; Vorobtsov, I.V.; Kuznetsov, A.V.; Savenkov, G.G.
Abstract: An investigation of high-rate deformation and spall fracture of some metals in a wide range of strain rate was carried out by using the Kolsky method and plane-wave shock experiment. The dynamic stress-strain curves were obtained and speed dependences of the strength characteristics were constructed for commercially pure aluminum and copper, as well as for stainless steel. The strength limits and their dependences on the strain rate and temperature are determined. Based on the obtained mechanical characteristics, the parameters of Johnson-Cook model for stainless steel were determined with due allowance for the influence of the strain rate and temperature on the yield surface radius. It is noted that the time dependence of the spall strength weakly dependent on temperature. A rationale is offered that explains the results within the framework of Zhurkov's kinetic theory of strength.